Effect of High-Flow Nasal Cannula Oxygen Therapy Versus Conventional Oxygen Therapy and Noninvasive Ventilation on Reintubation Rate in Adult Patients After Extubation: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (November 2018) - Huang, Hua-Wei; Sun, Xiu-Mei; Shi, Zhong-Hua; Chen, Guang-Qiang; Chen, Lu; Friedrich, Jan O.; Zhou, Jian-Xin
Purpose: We conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) to evaluate the effect of high-flow nasal cannula (HFNC) on reintubation in adult patients. Procedures: Ovid Medline, Embase, and Cochrane Database of Systematic Reviews were searched up to November 1, 2016, for RCTs comparing HFNC versus conventional oxygen therapy (COT) or noninvasive ventilation (NIV) in adult patients after extubation. The primary outcome was reintubation rate, and the secondary outcomes included complications, tolerance and comfort, time to reintubation, length of stay, and mortality. Dichotomous outcomes were presented as risk ratio (RR) with 95% confidence intervals (CIs) and continuous outcomes as weighted mean difference and 95% CIs. The random effects model was used for data pooling. Findings: Seven RCTs involving 2781 patients were included in the analysis. The HFNC had a similar reintubation rate compared to either COT (RR, 0.58; 95% CI, 0.21-1.60; P = .29; 5 RCTs, n = 1347) or NIV (RR, 1.11; 95% CI, 0.88-1.40; P = .37; 2 RCTs, n = 1434). In subgroup of critically ill patients, the HFNC group had a significantly lower reintubation rate compared to the COT group (RR, 0.35; 95% CI, 0.19-0.64; P = .0007; 2 RCTs, n = 632; interaction P = .07 compared to postoperative subgroup). Qualitative analysis suggested that HFNC might be associated with less complications and improved patient's tolerance and comfort. The HFNC might not delay reintubation. Trial sequential analysis on the primary outcome showed that required information size was not reached. Conclusion: The evidence suggests that COT may still be the first-line therapy in postoperative patients without acute respiratory failure. However, in critically ill patients, HFNC may be a potential alternative respiratory support to COT and NIV, with the latter often associating with patient intolerance and requiring a monitored setting. Because required information size was not reached, further high-quality studies are required to confirm these results.